Generation and characterization of a novel transgenic mouse harboring conditional nuclear factor-kappa B/RelA knockout alleles. Issue 1 (December 2016) - Ijaz, Talha; Wakamiya, Maki; Sun, Hong; Recinos, Adrian; Tilton, Ronald; Brasier, Allan
Abstract Background Nuclear Factor-Kappa B (NF-kB) is a family of transcription factors that are important in embryonic development, inflammation, epithelial-to-mesenchymal transition and cancer. The 65 kDa RelA subunit is the major transcriptional activator of the NF-kB pathways. Whole-body deficiency of RelA leads to massive apoptosis of liver hepatocytes and deathin utero . To study the role of RelA in physiology and in disease states in a manner that circumvents this embryonic lethal phenotype, we have generated a mouse with RelA conditional knockout (CKO) alleles containingloxP sites that are deleted by activated Cre recombinase. Results We demonstrate that RelACKO/CKO mice are fertile, do not display any developmental defects and can be crossed with Cre-expressing mice to delete RelA in a temporal, tissue-specific manner. Our mating of RelACKO/CKO mice with Zp3-Cre transgenic led to embryonic lethality of RelA-deficient embryos. In contrast, mating of RelACKO/CKO mice with Col1α2-CreER mice allowed for the generation of double transgenics which could be stimulated with tamoxifen to induce fibroblast-specific RelA deletion in adulthood. Conclusions Based on our collective data, we conclude that this novel RelACKO/CKO mouse allows for efficient deletion of RelA in a tissue-specific manner. This RelACKO/CKO mouse will be an invaluable tool for deciphering the mechanistic roles of RelA in various cells and tissues during development and in disease.